From Concept to Practice: Training in Person-Centered Care for People with Dementia - Maslow, Katie; Fazio, Sam; Ortigara, Anna; Kuhn, Daniel; Zeisel, John (Generations (San Francisco, Calif.), 2013)
This concluding article summarizes the majority of articles in the issue, notes areas of agreement and disagreement between them, and focuses on three ideas identified in articles eight through seventeen as most important for care providers to understand about person-centered care for people with dementia. It also summarizes the training needs noted in these articles and discusses public policies that could promote effective implementation of person-centered dementia care.